Therapeutic Potential of Cinnamon Oil: Chemical Composition, Pharmacological Actions, and Applications - Jiageng Guo; Xinya Jiang; Yu Tian; Shidu Yan; Jiaojiao Liu; Jinling Xie; Fan Zhang; Chun Yao; Erwei Hao (Pharmaceuticals)
Cinnamon oil, an essential oil extracted from plants of the genus Cinnamomum, has been highly valued in ancient Chinese texts for its medicinal properties. This review summarizes the chemical composition, pharmacological actions, and various applications of cinnamon oil, highlighting its potential in medical and industrial fields. By systematically searching and evaluating studies from major scientific databases including Web of Science, PubMed, and ScienceDirect, we provide a comprehensive analysis of the therapeutic potential of cinnamon oil. Research indicates that cinnamon oil possesses a wide range of pharmacological activities, covering antibacterial, anti-inflammatory, anti-tumor, and hypoglycemic effects. It is currently an active ingredient in over 500 patented medicines. Cinnamon oil has demonstrated significant inhibitory effects against various pathogens comprising Staphylococcus aureus, Salmonella, and Escherichia coli. Its mechanisms of action include disrupting cell membranes, inhibiting ATPase activity, and preventing biofilm formation, suggesting its potential as a natural antimicrobial agent. Its anti-inflammatory properties are evidenced by its ability to suppress inflammatory markers like vascular cell adhesion molecules and macrophage colony-stimulating factors. Moreover, cinnamon oil has shown positive effects in lowering blood pressure and improving metabolism in diabetic patients by enhancing glucose uptake and increasing insulin sensitivity. The main active components of cinnamon oil include cinnamaldehyde, cinnamic acid, and eugenol, which play key roles in its pharmacological effects. Recently, the applications of cinnamon oil in industrial fields, including food preservation, cosmetics, and fragrances, have also become increasingly widespread. Despite the extensive research supporting its medicinal value, more clinical trials are needed to determine the optimal dosage, administration routes, and possible side effects of cinnamon oil. Additionally, exploring the interactions between cinnamon oil and other drugs, as well as its safety in different populations, is crucial. Considering the current increase in antibiotic resistance and the demand for sustainable and effective medical treatments, this review emphasizes the necessity for further research into the mechanisms and safety of cinnamon oil to confirm its feasibility as a basis for new drug development. In summary, as a versatile natural product, cinnamon oil holds broad application prospects and is expected to play a greater role in future medical research and clinical practice.